PENGETAHUAN PERAWAT TENTANG KONSEP KEPERAWATAN HOLISTIK - Restu Ulfah S.; Madya Sulisno (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Holistic nursing practice related to nursing knowledge. Knowledges the foundation of nursing actions and is one component of a healer in nursing care. This research’s pupose is to provide information about nurse’s knowledge of holistic concept in nursing care. This research used quantitative research with descriptive survey design. Respondent of this research 134 nurses with used total sampling. The data was collected with spread the holistic nursing knowledge questionnaires. The results of this ressearch showed the level of nurse’s knowledge in medium level with each percentage of knowledge is personal 39,6%, empirical 42,5%, aesthetics 53%, ethics 50,7%. Knowledge in less level is unknowing 52,2% andsociopolitical44,8%. This research provide information about nurse’s knowledge of holistic concept in nursing care. Holistic nursing knowledge need the expansion ofinformation to nurses for be applied in nursing care practice